THE INFLUENCE OF ECONOMIC GROWTH, REGIONAL ORIGINAL INCOME (PAD) AND GENERAL ALLOCATION FUNDS (DAU) ON CAPITAL EXPENDITURE BUDGET ALLOCATION (Case Study in Districts and Cities in North Sumatra Province 2015-2017) - Desi Vuspa Andriani Hasibuan; Arni Karina; Kumba Digdowiseiso (Jurnal Ekonomi, 2023)
This research aims to analyze whether Economic Growth, Regional Original Income (PAD) and General Allocation Funds (DAU) have a positive effect on Capital Expenditures in Regencies and Cities of North Sumatra Province. Research contributions can provide information about the importance of optimizing local potential in regions to improve the quality of public services and the concept of decentralization can be realized so that regional governments do not continue to depend on the central government. The results of this research show that Economic Growth partially has a negative and insignificant effect on Capital Expenditures, while Regional Original Income (PAD) and General Allocation Funds (DAU) partially have a positive and significant effect on Capital Expenditures. Simultaneously Economic Growth, Regional Original Income and General Allocation Funds have a positive and significant effect on Capital Expenditures.